Land Lapse Phenomenon and Surface Subsidence Law of Shield Tunnel Passing Through Rock-Bearing Formation - Guangming, Yu; Pengju, Xia; Yongyi, Zhang; Qimeng, Shi; Jun, Lei; Pengfei, Song; Zhiwen, Tan; Hao, Liu; Ze, Chen (Frontiers in Earth Science, 2022)
When building metro tunnels in coastal cities, we often encounter boulders with high strength and large volume.A large number of engineering practices have shown that the existence of boulders will destroy the singleness and uniformity of the stratum. If the tunnel crossing the construction is handled improperly, it will lead to surrounding rock collapse, which may cause ground collapse, damage to surrounding buildings and other problems, and endanger the safety of people's lives and property. Firstly, with the simulation test of similar materials, The scene reproduces the vault collapse and surface collapse when the tunnel crosses the stone formation, explore the law of formation collapse and surface subsidence caused by solitary rock during tunnel tunneling; Secondly, taking the tunnel project of Shenzhen Metro Line 13 as an example, Midas GTS NX numerical simulation software is used to compare and analyze the influence characteristics of boulder on surrounding rock deformation and surface settlement; Lastly, organize and summarize the engineering treatment measures for the tunnel of Shenzhen Metro Line 13, the research results are of great significance to guide the prediction and disposal of surface subsidence in tunnel construction projects.